Evidence-based therapy for knee osteoarthritis: expected short-, medium-, and long-term outcomes of prescription crystalline glucosamine sulfate administration - L. N. Denisov; L. I. Alekseeva; E. G. Zotkin; I. S. Dydykina; A. M. Lila; S. S. Rodionova; A. Yu. Kochish; E. A. Trofimov; E. Z. Yakupov; S. P. Yakupova; L. N. Eliseeva (Современная ревматология)
The need for effective drugs for the treatment of knee osteoarthritis (OA) is constantly growing. Current guidelines recommend the use of symptomatic slow acting drugs for osteoarthritis (SYSADOA) such as glucosamine (GCA) in this disease. Among various drugs containing GCA, high bioavailability and clinical efficacy have been shown only for prescription crystalline GCA sulfate (pGCAS) administration. Several meta-analyses and network meta-analyses have shown that efficacy of pGCAS 1500 mg once daily is superior to other GCA-based products (such as GCA hydrochloride with or without sodium sulfate) and the combination of GCA with chondroitin sulfate (CS) in terms of reducing the intensity of pain and improving the functional state. These studies confirmed the favorable safety profile of pGCAS, which was comparable to placebo in the incidence of adverse events. Pharmacoeconomic studies have also demonstrated greater cost-effectiveness of pGCAS compared to other GCA drugs.A group of Russian experts at a meeting of the advisory committee reviewed the evidence in favor of the use of pGCAS and evidence of its effectiveness in the treatment of knee OA in comparison with other products that include GCA, and the fixed combination of GCA with CS. Taking into account the results obtained, the use of pGCAS at a dose of 1500 mg once a day is recommended as a rational choice for the treatment of knee OA.